From Benchmarking to Meaning-Making: A Conceptual Framework for Integrating SDG 4 into CEFR-Based Speaking Materials in Higher Education - Kalsum Kalsum; Rahimah Saimin; Engku Muhammad Syafiq Engku Sharfuddin (Indonesian TESOL Journal, 2026)
University speaking programmes increasingly adopt the Common European Framework of Reference for Languages (CEFR) to guide curriculum and assessment. However, existing implementation has largely emphasized assessment alignment, while the integration of sustainability and inclusion into CEFR-based speaking materials remains conceptually underdeveloped. This imbalance represents both a theoretical gap, as little attention has been paid to connecting CEFR's action-oriented philosophy with Education for Sustainable Development (SDG 4), and a practical gap, as materials developers lack systematic guidance for embedding these values into speaking instruction. Addressing this gap, this conceptual study develops an evidence-informed framework for integrating SDG 4 into CEFR-based speaking materials in higher education. The framework was constructed through a design-oriented conceptual analysis that systematically translated evidence synthesized from a previous systematic review and relevant theoretical literature into design requirements, which were subsequently consolidated into overarching design principles and organized into a coherent framework. The analysis generated five interrelated principles: thematic authenticity, descriptor-anchored task design, mediation as a vehicle for values, inclusive differentiation, and the separation of language assessment from content engagement. These principles were organized into a five-layer materials-development framework comprising descriptor literacy, SDG 4 thematic mapping, action-oriented task cycles, assessment integrity, and institutional support. Unlike the previously proposed Integrated CEFR Implementation Framework, which focuses on system-level implementation, the proposed framework contributes a product-level model to guide the development of sustainability-oriented CEFR-based speaking materials and is intended to serve as a conceptual foundation for future materials development and empirical validation in Indonesian higher education and comparable multilingual EFL contexts.